STRATEGI REHABILITASI ANAK JALANAN MELALUI PENDIDIKAN KESETARAANPAKET B DI KELOMPOK BELAJAR SUKET TEKI KELURAHAN KALIOMBOKECAMATAN KOTA KOTA KEDIRI - SRI RAHAYU (JPUS: Jurnal Pendidikan Untuk Semua, 2018)
The street children is one of serious phenomone today, they are must be basic of govermant fondation. They must be stay at schol, find the knowledge for their future life, for their age is  too early to find the money, their time must enough for study, do not on the strret. The purpose for this research is for discription about How the rule of non formal educatian for Suket Teki Learning Community, to know the caracteristic steet children who learn at this Comunity, and descript what the strategi rehabitation for street children at Suket Teki Laerning Community.This research use the qualitative approach, using the deep interview, and directly obsevation. The result this reserach is Non formal education concep at Suket Teki Community Leraning is different with the other, this community used the comfortable time and place, study make enjoy and fun, this comunity learning fillso much the caracter material and life skill, the purpose this method hope that the student is not camback to the street, get the sertificate,  they can find the job individualy and join with their society easily.